Effects of Pediatric Burns on Gastrointestinal Diseases: A Population-Based Study - Boyd, James; Wood, F.; Randall, Sean; Fear, M.; Rea, S.; Duke, J. (Lippincott Williams and Wilkins, 2017)
Copyright Â© 2016 by the American Burn Association. The systemic responses triggered by burns have been shown to include effects on the gastrointestinal tract. However, it is not clear if these changes lead to long-term gastrointestinal morbidity in patients with burns. The aim of this study was to assess if pediatric burns are associated with increased hospital use for gastrointestinal diseases after discharge for the initial injury. A population-based longitudinal study was performed using linked hospital and death data from Western Australia for children younger than 15 years when hospitalized for a first burn injury (n = 10,436) between 1980 and 2012, along with a frequency-matched noninjury comparison cohort, randomly selected from Western Australia's birth registrations (n = 40,819). Crude admission rates and cumulative length of stay for digestive diseases were calculated. Negative binomial and Cox proportional hazards regression modeling were used to generate incidence rate ratios (IRRs) and hazard ratios, respectively. After discharge, the pediatric burn cohort experienced twice the rate of gastrointestinal disease admissions (IRR, 95% confidence interval [CI]: 2.03, 1.56-2.65), spent over twice as long in hospital (IRR, 95% CI: 2.23, 1.67-2.98), and had a higher rate of first-time or incident gastrointestinal disease admissions (hazard ratio, 95% CI: 1.18, 1.08-1.29) when compared with the uninjured cohort, after adjusting for demographic and preexisting health factors. Children who experience a burn injury hospitalization are at increased risk of postburn hospital service use for gastrointestinal diseases when compared with uninjured children.